Qualidade de vida de adolescentes e adultos jovens vivendo com HIV/aids e sua associação com aspectos clínicos e adesão ao tratamento - Carneiro, Rebeca Rocha (2019)
With the advent of high-potency antiretroviral therapy (ART), unequivocal benefits for reducing AIDS related morbidity and mortality, the increased survival of people living with HIV/AIDS has become a reality and these infected people have become concerned about their quality of life. Knowing and understanding the physical, psychological and social conditions that involve the patient, represents an important and indispensable tool for approaching people who live with this condition. In this context, adolescents and young adults who experience HIV and AIDS and its treatment so early stand out. Objective: to assess the health-related quality of life of adolescents and young adults living with HIV/AIDS and its association with clinical aspects, affective-sexual life and adherence to treatment. Method: Analytical and descriptive study, cross-sectional and quantitative in nature; held at a referral hospital for infectious diseases in the state of Paraíba, located in the city of João Pessoa – PB. Data were collected from February to May 2019. The population consisted of adolescents and young adults living with HIV/AIDS who were being followed up on an outpatient basis in this hospital and the sample involved 76 users. For data collection, a structured questionnaire was used containing sociodemographic, affective-sexual and clinical information, and specific instruments for assessing quality of life, the World Health Organization Quality of Life, shortened version (WHOQOL-HIV-Bref) and Scale Adherence to Treatment (CEAT-HIV). The data were analyzed using descriptive statistics, a Binary Logistic Regression model and a weight-based model of evidence, the Weight of Evidence (WoE). Results: Among the participants, there was an average age of 19 years, with a greater number of cases in the age group between 22 and 24 years; the majority are men (84.21%), single (73.69%), do not profess any kind of faith (50%) and the majority have completed high school (28.95%). With regard to affective-sexual life, the results demonstrate some types of vulnerability to which adolescents and young adults living with HIV/AIDS are exposed, where the majority are self-declared homosexual and the main form of exposure to HIV/AIDS was sexual , a representative portion reports not having a steady partner, remains in short-term relationships, sexual partners are unaware of their HIV-positive status, maintain relationships with HIV-negative individuals and use condoms discontinuously. In a WHOQOL-HIV-Bref analysis, the total quality of life score had a median equal to 66.38. Among the domains of the instrument, the most affected were the environment and psychological domains and the one that represents the best score was the physical domain. From the logistic regression model, it was possible to identify the variables that have a negative impact on quality of life, identifying as factors that decrease the chance for good quality of life: not having religion and being hospitalized. On the other hand, the model pointed out that having adherence to ART, being male, relating to a serodiscordant partner and having some type of religion are factors that increase the quality of life. There is a correlation between all domains of quality of life and adherence to ART. The generated WoE model contributes to strengthening the evidence pointed out by the logistic regression models for each domain, reinforcing in almost all domains the association between adherence to antiretroviral therapy and quality of life. Conclusion: The development of this investigation is opportune so that information about the epidemiology and the factors that interfere in the quality of life of this population are available to support decision-making by health professionals and related in order to prevent and control the factors that may affect the quality of life and adherence to the treatment of these people, fundamental characteristics for better living conditions after infection by the HIV virus.